2008
DOI: 10.1007/s10875-008-9196-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sirolimus in IPEX and IPEX-Like Children

Abstract: Our patients exhibited features of enteropathy and recurrent infections with bacterial and viral pathogens. Before initiating sirolimus, six patients were treated with corticosteroids. Several also received other immunosuppressive agents. After starting sirolimus, six patients had improvement in diarrhea, and two were able to decrease corticosteroid dosages. Several also had significantly decreased number of infections after treatment. Of the three patients with post-treatment duodenal biopsies, two showed imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 25 publications
1
55
0
2
Order By: Relevance
“…Currently available treatments including steroids and cyclosporine have resulted in remission only in a subset of patients, then large doses of steroids are often necessary to control active disease. Patients with autoimmune entheropathy commonly do not respond to conventional treatment or other non-specific (26,27), there was no evidence of using sirolimus in treatment of enteropathy in LRBA deficient patients. In the current study, for the first time, four LRBA deficient patients unresponsive to non-specific immune-suppressive agents underwent sirolimus therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently available treatments including steroids and cyclosporine have resulted in remission only in a subset of patients, then large doses of steroids are often necessary to control active disease. Patients with autoimmune entheropathy commonly do not respond to conventional treatment or other non-specific (26,27), there was no evidence of using sirolimus in treatment of enteropathy in LRBA deficient patients. In the current study, for the first time, four LRBA deficient patients unresponsive to non-specific immune-suppressive agents underwent sirolimus therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Araki et al (25) found that treatment of a severe refractory colonic and perianal Chrone's disease with sirolimus may result in a marked improvement in symptoms of enteropathy. Yong et al (26) also reported the impact of sirolimus in children with IPEX and IPEX-like entheropathy. Although satisfying results of adprovement in the patients' weight.…”
Section: Case Presentationmentioning
confidence: 98%
“…Неко-торые авторы описывают положительный эффект иммуносупрессивных препаратов (циклоспорин А, такролимус, сиролимус и т.д. ), которые позволяют частично контролировать аутоиммунные наруше-ния [24,25]. Наиболее перспективным направлени-ем в терапии IPEX-синдрома считается пересадка костного мозга [11,26].…”
Section: Discussionunclassified
“…С целью коррекции имму-нодефицита возможно применение иммуносупрес-сивной монотерапии (циклоспорин А, такролимус) или комбинированной -сочетание иммуносупрес-сивных препаратов со стероидными. Сиролимус (рапамицин) показал свою эффективность, у не-скольких пациентов наблюдалась стойкая ремиссия заболевания [6,22]. Кроме иммуносупрессивной, проводится заместительная терапия эндокринных нарушений, адекватная нутриционная поддержка, симптоматическая терапия.…”
unclassified